1978
DOI: 10.1001/jama.1978.03290060047012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammatory Gingival and Periodontal Disease

Abstract: Gingivitis and periodontitis account for more than 95% of all inflammatory diseases of the tissues surrounding the teeth, comprising the principal cause of tooth loss in adults. Gingivitis is a relatively innocuous inflammation of the gums, with associated bleeding and exudation. Gingivitis may convert to periodontitis, a destructive aggressive disease with resorption of alveolar bone, destruction of collagen with fibrosis, and formation of deep pockets around the necks of the teeth. Gingivitis and periodontit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 4 publications
0
25
0
1
Order By: Relevance
“…This subsequently leads to damage to the surrounding gingival tissues and supporting structures of the tooth. It varies in severity from reversible gingivitis to severe irreversible periodontitis, where the periodontal ligaments and alveolar bone are destroyed [28]. Despite our ability to easily prevent this disease with oral hygiene measures, it remains one of the most prevalent diseases in the world, with nearly half of adults in the USA developing periodontitis [29].…”
Section: Periodontal Disease: An Uncontrolled Ganglandmentioning
confidence: 99%
“…This subsequently leads to damage to the surrounding gingival tissues and supporting structures of the tooth. It varies in severity from reversible gingivitis to severe irreversible periodontitis, where the periodontal ligaments and alveolar bone are destroyed [28]. Despite our ability to easily prevent this disease with oral hygiene measures, it remains one of the most prevalent diseases in the world, with nearly half of adults in the USA developing periodontitis [29].…”
Section: Periodontal Disease: An Uncontrolled Ganglandmentioning
confidence: 99%
“…9 Periodontitis is one of the most widespread inflammatory diseases, characterized by gingival bleeding, periodontal pocket formation, destruction of connective tissue attachment, and alveolar bone resorption. 13,14 Many studies have demonstrated that atherosclerosis and periodontitis are associated and possibly causally linked. [15][16][17][18][19] Therefore, it is possible that periodontitis augments the effects of obesity on atherosclerosis.…”
mentioning
confidence: 99%
“…A rapid increase of ATP concentration in the extracellular environment is a danger signal which alerts immune cells of an impending threat, and mobilizes a rapid inflammatory response to clear invading pathogens. Exacerbated host inflammatory response against plaque bacteria lead to hallmark features of periodontal disease including gingival inflammation, pocket formation, tissue damage, and alveolar bone loss (Page et al, 1978). Presence of ATP in the extracellular environment has been shown to exacerbate periodontitis.…”
Section: Introductionmentioning
confidence: 99%